1998
DOI: 10.1029/98jb02129
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotelluric imaging of the Society Islands hotspot

Abstract: Abstract. In April-June 1989, seafloor magnetotelluric data across and along the leading edge of the Tahiti hotspot were obtained. The magnetotelluric response functions were found to be strongly influenced by bathymetric and island effects, and a new procedure for modeling and removing this distortion using a thin sheet approach combined with the measured water depths is introduced. The corrected response functions are consistent with a two-dimensional structure. Inversion of the data shows a slightly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 88 publications
2
73
0
2
Order By: Relevance
“…1, modified from Suetsugu et al, 2009). The small-scale anomalies, possibly mantle plumes, are present beneath the Society and Macdonald hotspots, which agrees with the results obtained from early magnetotelluric tomography (Nolasco et al, 1998). However, the explanation remained unclear because the insufficient station coverage impeded the investigation of the anomaly routes to the hotspots and their depth extents.…”
Section: Introductionsupporting
confidence: 78%
“…1, modified from Suetsugu et al, 2009). The small-scale anomalies, possibly mantle plumes, are present beneath the Society and Macdonald hotspots, which agrees with the results obtained from early magnetotelluric tomography (Nolasco et al, 1998). However, the explanation remained unclear because the insufficient station coverage impeded the investigation of the anomaly routes to the hotspots and their depth extents.…”
Section: Introductionsupporting
confidence: 78%
“…일반적으로 심부지각 구조를 조사하기 위해서는, 자연송신원 자기지전류(MT; Magnetotelluric) 탐사가 폭넓게 활용된다 (Jones, 1999;Jones and Ferguson, 2001 (Nolasco et al, 1998;Santos et al, 2001;Yang et al, 2010 …”
Section: 서 론unclassified
“…The correction method is further classified into approaches with or without forward modeling. For the approach with forward modeling, the electromagnetic fields are modeled for a resistivity structure with and without topography to acquire distortion terms which are used for the correction (e.g., Nolasco et al, 1998). On the other hand, for the approach without forward modeling, tensor decomposition is frequently used because of its availability, esCopyright c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB.…”
Section: Introductionmentioning
confidence: 99%
“…These differences are caused by differences in treatment of the distortions of magnetic field and in robustness of the correction equation to a resistivity structure assumed for the topographic correction. The results suggest that the correction equation of Nolasco et al (1998) should be used because it better accommodates the estimation of unknown resistivity structures. We apply the correction equation of Nolasco et al (1998) to a response observed in the Mariana area.…”
mentioning
confidence: 99%
See 1 more Smart Citation